Disparate Roles of Oxidative Stress in Rostral Ventrolateral Medulla in Age-Dependent Susceptibility to Hypertension Induced by Systemic l-NAME Treatment in Rats - Chao, Yung-Mei; Rauchová, Hana; Chan, Julie Y H (Biomedicines, 2022)
This study aims to investigate whether tissue oxidative stress in the rostral ventrolateral medulla (RVLM), where sympathetic premotor neurons reside, plays an active role in age-dependent susceptibility to hypertension in response to nitric oxide (NO) deficiency induced by systemic l-NAME treatment, and to decipher the underlying molecular mechanisms. Systolic blood pressure (SBP) and heart rate (HR) in conscious rats were recorded, along with measurements of plasma and RVLM level of NO and reactive oxygen species (ROS), and expression of mRNA and protein involved in ROS production and clearance, in both young and adult rats subjected to intraperitoneal (i.p.) infusion of l-NAME. Pharmacological treatments were administered by oral gavage or intracisternal infusion. Gene silencing of target mRNA was made by bilateral microinjection into RVLM of lentivirus that encodes a short hairpin RNA (shRNA) to knock down gene expression of NADPH oxidase activator 1 (Noxa1). We found that i.p. infusion of l-NAME resulted in increases in SBP, sympathetic neurogenic vasomotor activity, and plasma norepinephrine levels in an age-dependent manner. Systemic l-NAME also evoked oxidative stress in RVLM of adult, but not young rats, accompanied by augmented enzyme activity of NADPH oxidase and reduced mitochondrial electron transport enzyme activities. Treatment with L-arginine via oral gavage or infusion into the cistern magna (i.c.), but not i.c. tempol or mitoQ10, significantly offset the l-NAME-induced hypertension in young rats. On the other hand, all treatments appreciably reduced l-NAME-induced hypertension in adult rats. The mRNA microarray analysis revealed that four genes involved in ROS production and clearance were differentially expressed in RVLM in an age-related manner. Of them, Noxa1, and GPx2 were upregulated and Duox2 and Ucp3 were downregulated. Systemic l-NAME treatment caused greater upregulation of Noxa1, but not Ucp3, mRNA expression in RVLM of adult rats. Gene silencing of Noxa1 in RVLM effectively alleviated oxidative stress and protected adult rats against l-NAME-induced hypertension. These data together suggest that hypertension induced by systemic l-NAME treatment in young rats is mediated primarily by NO deficiency that occurs both in vascular smooth muscle cells and RVLM. On the other hand, enhanced augmentation of oxidative stress in RVLM may contribute to the heightened susceptibility of adult rats to hypertension induced by systemic l-NAME treatment.
Keywords: l-NAME; mitochondria; NADPH oxidase activator 1; nitric oxide; aging; rostral ventrolateral medulla; hypertension; reactive oxygen species